Field research in political science : practices and principles - Kapiszewski, Diana; MacLean, Lauren M.; Read, Benjamin Lelan (Cambridge : Cambridge University Press, 2015)
Field research - leaving one's home institution in order to acquire data, information or insights that significantly inform one's research - remains indispensable, even in a digitally networked era. This book, the first of its kind in political science, reconsiders the design and execution of field research and explores its role in producing knowledge. First, it offers an empirical overview of fieldwork in the discipline based on a large-scale survey and extensive interviews. Good fieldwork takes diverse forms yet follows a set of common practices and principles. Second, the book demonstrates the analytic benefits of fieldwork, showing how it contributes to our understanding of politics. Finally, it provides intellectual and practical guidance, with chapters on preparing for field research, operating in the field and making analytic progress while collecting data, and on data collection techniques including archival research, interviewing, ethnography and participant observation, surveys, and field experiments.
1. Field research in political science: practices and principles -- 2. A historical and empirical overview of field research in the discipline -- 3. Preparing for fieldwork -- 4. Managing in the field: logistical, social, operational, and ethical challenges -- 5. Thinking outside the (archive) box: discovering data in the field -- 6. Interviews, oral histories, and focus groups -- 7. Site-intensive methods: ethnography and participant observation -- 8. Surveys in the context of field research -- 9. Experiments in the field -- 10. Analyzing, writing, and retooling in the field -- 11. The future of field research in political science.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Political science -- Fieldwork; Political science -- Research; Political science -- Research -- Methodology